A galactic microquasar mimicking winged radio galaxies. Issue 1 (December 2017) - Martí, Josep; Luque-Escamilla, Pedro; Bosch-Ramon, Valentí; Paredes, Josep
Abstract A subclass of extragalactic radio sources known as winged radio galaxies has puzzled astronomers for many years. The wing features are detected at radio wavelengths as low-surface-brightness radio lobes that are clearly misaligned with respect to the main lobe axis. Different models compete to account for these peculiar structures. Here, we report observational evidence that the parsec-scale radio jets in the Galactic microquasar GRS 1758-258 give rise to aZ -shaped radio emission strongly reminiscent of theX andZ -shaped morphologies found in winged radio galaxies. This is the first time that such extended emission features are observed in a microquasar, providing a new analogy for its extragalactic relatives. From our observations, we can clearly favour the hydrodynamic backflow interpretation against other possible wing formation scenarios. Assuming that physical processes are similar, we can extrapolate this conclusion and suggest that this mechanism could also be at work in many extragalactic cases. Winged radio galaxies possess wing features detectable at radio wavelengths, yet the physical interpretation of such extragalactic radio sources remains elusive. Here, the authors report the observation of a downsized Z -shaped radio emission from the Galactic microquasar GRS 1758-258, shedding light on the formation of wings in radio galaxies given its strongly reminiscent winged morphology.